Alternative Deep Basement Solutions for Built- Up Areas - Abid Adekunte (Deep Foundations Institute, 2015)
"In recent years, developers have had to deal with complexities associated with numerous cases of deep basement construction in built-up areas. Design and construction of deep excavation support systems in urbanised zones come with many technical challenges. Restricted working spaces often render the use of temporary struts as wall restraint systems unpopular, as working space needs to be maximised. Also, tie-back anchors are often inapplicable due to the existence of adjacent structures. Therefore, developing alternative restraint systems for deep basement structures in builtup areas is becoming increasingly important to the present day basement engineer.This paper is centred on the design, construction and monitoring of enabling works for deep basement structures on three sites in the United Kingdom and Republic of Ireland. Traditional tieback anchorage and propping systems were inapplicable on the sites. As alternatives, separate novel wall restraint systems were developed and adopted, to enable excavation on each of the three sites.Performances of the novel wall restraint systems, as well as the responses of adjacent structures were monitored. Numerical modelling and field monitoring results show the three alternative wall restraint systems to be safe and effective. The paper also highlights the advantages of the novel solutions over conventional methods.INTRODUCTIONRecently, deep basement structures have become popular components of urban building developments. As pointed out by Pearlman et al., 2004, this could be attributed to the inadequacy of surface parking spaces in urbanised zones, while underground parking facilities are also believed to improve both aesthetic and commercial qualities of urban structures.However, while the incorporation of basement structure into new urban development appeals to developers and architects, the engineering design and construction aspects of basement works typically come against a whole lot of complexities and challenges. As highlighted by Wong, 2002, engineering problems associated with basement construction in built-up areas are numerous, some of these include; complicated sub-soil conditions, dealing with excessive active pressures, complex temporary works, proximity of sensitive adjacent structures, high level hazards to construction workmen and surrounding community, inadequate working space, etc."